'Between two wars - coal', 1942 (1942)
1942 1939-1945 "'Between two wars - coal', 1942" [HFR0233], 1942 This Labour Party pamphlet by James Griffiths blames the crisis in coal production in the early years of the war on the failure to implement the recommendation of the 1919 Coal Industry Commission on nationalisation. The Foreword of the pamphlet is written by Will Lawther, President of the Mineworkers' Federation.